Statistical tests of the rank of a matrix and their applications in econometric modelling - Gonzalo Camba-Mendez; George Kapetanios (Queen Mary University of London, Department of Economics, 2005)
Testing the rank of a matrix of estimated parameters is key in a large variety of econometric modelling scenarios. This paper describes general methods to test for the rank of a matrix, and provides details on a variety of modelling scenarios in the econometrics literature where these tests are required.
Keywords: C12; C15; C32; 330; Multiple time series; Model specification; Tests of rank; Zeitreihenanalyse; Matrizenrechnung; Ranking-Verfahren